Documents of protest and compassion : the poetry of Walter Bauer - Arend, Angelika, 1942- (McGill-Queen's University Press, 1999)
Documents of Protest and Compassion offers the first extensive critical assessment of Bauer's considerable poetic oeuvre. In this long-overdue supplement to recent anthologies of Bauer's poetry and essays on his life and work, Angelika Arend draws on Bauer's diaries and letters to reveal the profoundly humane intentions that guided his choice of themes and structures. She shows that social protest and brotherly compassion, shared responsibility and critical self-reflection are Bauer's main thematic fare, which he presented in simple, yet carefully crafted, poetic structures, and explains how these ideas and forms developed or remained constant in light of historical, cultural, social, and personal developments. Documents of Protest and Compassion is important for those interested in Bauer's work, German poetry, German-Canadian literature, and the immigrant writing experience.